Time‐lag in extinction dynamics in experimental populations: evidence for a genetic Allee effect?. (7th February 2013) - Vercken, Elodie; Vincent, Flora; Mailleret, Ludovic; Ris, Nicolas; Tabone, Elisabeth; Fauvergue, Xavier; Gurney, William
Summary Propagule pressure, i.e. the number of individuals introduced, is thought to be a major predictor of the establishment success of introduced populations in the field. Its influence in laboratory experimental systems has however been questioned. In fact, other factors involved in long‐term population persistence, like habitat size, were usually found to explain most of the dynamics of experimental populations. To better understand the respective influence of short‐ and long‐term factors and their potential interaction on extinction dynamics in experimental systems, we investigated the influence of propagule pressure, habitat size and genetic background on the early dynamics of laboratory‐based populations of a hymenopteran parasitoid. The amount of demographic variance differed between establishment and persistence phase and was influenced by habitat size and genetic background (geographic strain), but independent of propagule pressure. In contrast, the probability of extinction within five generations depended on the genetic background and on the interaction between propagule pressure and habitat size. Vulnerability to extinction in small size habitats was increased when populations were founded with a small number of individuals, but this effect was delayed until the third to fifth generations. These results indicate that demographic stochasticity is influential during population establishment, but is not affected by the genetic variability of propagules. On the other hand, extinction might be influenced by a genetic Allee effect triggered by the combination of low propagule pressure and genetic drift. Finally, we documented consistent differences between genetic backgrounds in both deterministic and stochastic population dynamics patterns, with major consequences on extinction risk and ultimately population establishment.